STUDI KOMPARASI STRUKTUR KURIKULUM PENDIDIKAN KEWARGANEGARAAN DI TIGA PROVINSI KANADA (ONTARIO, SASKATCHEWAN, DAN BRITISH COLUMBIA) - Istiqomah, Annisa (IKIP PGRI PONTIANAK, 2017)
Canadian multicultural society emphasizes the form of Citizenship Education implementation whose implementation authority is assigned to each province. Each province in Canada has different jurisdictions in the implementation process of Citizenship Education. Conceptions of citizenship and Citizenship Education form the basis of policy in Canada's state school curriculum referring to activists at the end of each study. There are different perspectives of Citizenship Education in each community in different provinces such as Ontario, British Columbia and Saskatchewan. This is allegedly an implication of the policy of regional autonomy in conducting education affairs. Citizenship Education in Canada is integrated with all components of social studies. The curriculum policy of Citizenship Education considers that good Canadians are individuals who have knowledge of contemporary society and the issues it faces; work towards the common good; support pluralism; and are skilled at taking action to make their community, nation, and world a better place for everyone.